Hubungan Model Pembelajaran Teams Games Tournaments (TGT) Dengan Keaktifan Belajar Pendidikan Agama Kristen (PAK) Siswa Kelas XI SMK Negeri 1 Siborongborong Tahun Pembelajaran 2023/2024 - Lestari Gloria Marbun; Dame Taruli Simamora; Helena Turnip; Robinhot Robinhot; Rida Gultom (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
This research aims to determine the positive and significant relationship between the Based Learning Model and the Learning Activeness of PAK class XI students at SMK Negeri 1 Siborongborong for the 2023/2024 academic year. The method used in this research is a descriptive quantitative research method. The population is all students of class The instrument for this research is a closed questionnaire. The instrument for this research is a closed questionnaire. From the results of the calculation of the positive relationship test, it is obtained that the rcount value is rcount=0.566> rtable=0.344, thus it is known that there is a positive relationship between variable which is significant between variable